Polarization holography - Nikolova, L. (Cambridge University Press, 2009)
Current research into holography is concerned with applications in optically storing, retrieving, and processing information. Polarization holography has many unique properties compared to conventional holography. It gives results in high efficiency, achromaticity, and special polarization properties. This books reviews the research carried out in this field over the last 15 years. The authors provide basic concepts in polarization and the propagation of light through anisotropic materials, before presenting a sound theoretical basis for polarization holography. The fabrication and characterization of azobenzene based materials, which remain the most efficient for the purpose, is described in detail. This is followed by a description of other materials that are used in polarization holography. An in-depth description of various applications, including display holography and optical storage, is given, and the book concludes with perspectives for the future. This book is an important reference for researchers.